Peter Eisenman : transcripción de teleconferencia con el arquitecto. - Gómez Benítez, Werner; Pérez, Roberto; Angulo, Carlos; Acosta, Nohora; Forero La Rotta, Augusto; Martínez Segura, Germán (Revista de Arquitectura (Bogotá), 2000)
-